Allium affine Extract Improves Dexamethasone-Induced Hyperlipidemia in Rats - Masoud Sadeghi Dinani; Leila Safaeian*; Moosa Mohsen; Yasaman Mohammadzamani (Iranian Society of Pharmacognosy, 2023)
Background and objectives: Various Alliumplants were found to improve blood lipid profile. The present investigation explored the anti-hyperlipidemic potential of A. affine in a rat model of hyperlipidemia induced by glucocorticoid. Methods: Hydroalcoholic extract was prepared by maceration method and assessed for total phenolic content. Forty-eight male Wistar rats in eightgroups were studied. Group I received vehicle; group II was treated only with 400 mg/kg A. affine orally; group III was subcutaneously injected with 10 mg/kg/day dexamethasone; group IV as the reference group received dexamethasone and 40 mg/kg atorvastatin orally; groups V-VIII were treated with dexamethasone and simultaneously with 50, 100, 200 or 400 mg/kg of A. affine extract orally. All treatments were done over a period of seven days. Blood levels of glucose, lipid profile, liver enzymes and malondialdehyde (MDA) were assessed in over-fasted rats. Liver tissues were weighed and evaluated for histopathologicalalterations. Results: The amount of total phenolics content of A. affine extract was 11.24 ± 1.7 mg/g as gallic acid equivalent. Administration of A. affineextract significantly lowered the blood levels of triglycerides, total cholesterol, low-density lipoprotein (LDL)-cholesterol, very low-density lipoprotein (VLDL)-cholesterol, blood sugar, aspartate aminotransferase (AST), alanine aminotransferase (ALT) and MDA. However, there was no significant effect on high-density lipoprotein (HDL)-cholesterol level. A. affineimproved hepatic steatosis resulted from dexamethasone. Conclusion: These findings suggest potential of A. affine for preventing and managing hyperlipidemia. However, more trials are needed concerning its clinical efficacy and identifying its bioactive phytochemicals and mechanisms participated in the lipid-lowering action.